Prospects of Reform of the WTO Dispute Settlement Mechanism - El Khoury, Maya (UI Scholars Hub, 2011)
In a context of economic globalization, the WTO emerged within the multilateral trading system as an international organization settling intergovernmental trade disputes. The WTO dispute settlement mechanism is rather an enhanced adaptation of its predecessor as it developed into an institutionalized and semi-judicialized system. the evaluation of the dispute settlement mechanism would contribute to a better understanding of the WTO as an international organization and its influence on the development of the international economic law. In general, three different movements occurred throughout the life of the dispute settlement mechanism, thus distinguishing its practice under the GATT and the WTO correspondingly: the emergence of a semi-judicial institution; the enhancement of the access to justice by developing countries; and the reinforcement of the implementation phase. With these three movements in sight, this article intends to investigate whether the WTO dispute settlement mechanism can still satisfy the needs of predictability and safety as defined by Article 3 of the DSU.